School-Issued Devices for Home Use in Kindergarten through 5th Grade and Parent Perceptions of Child Learning, Behavior, and Conflict - Brandon T. McDaniel; Nathalie Gullo; Zachary Kaiser; Lauren Reining; I. Joyce Chang; Michelle Drouin (Human Behavior and Emerging Technologies)
With many U.S. schools adopting 1-to-1 school device programs, research on the potential impacts of this device usage at home is critical. In this study, we examined elementary school parents’ perceptions of their child’s use of their school-issued device for academic skill-building and entertainment at home. We then examined the associations between these different types of use and children’s learning, behavior, and parent-child conflict over the device use. Overall, we found that children’s use of school devices at home for building academic skills was predictive of positive impacts on learning and child behaviors and less frequent parent-child conflict over use. In contrast, children’s use of school devices for entertainment purposes was associated with negative impacts on learning and child behaviors and more frequent parent-child conflict over use. Additionally, although most parents received some training or resources, many parents felt that device training from schools was insufficient, and parent perceptions of insufficient training were related to less use of the device for academic purposes and greater parent-child conflict. Considering this duality, we offer suggestions for training by schools, which training emphasizes effective child use of school-issued devices within the home.